Implementation of Hadith Contextual Approach in Legal Istinbath - Muhammad Hilmi Syukri; Nur Hidayat; Khayyu Anggun Maharani (AJIS: Academic Journal of Islamic Studies, 2023)
This research was conducted because mistakes often occur in taking legal istinbath when understanding a hadith.This study discusses how the legal istinbath of a hadith takes into account the socio-cultural conditions to whom the hadith is conveyed.This research uses the maktabiyah study method, in other words, to explore information that refers to books or literacy related to the discussion. The results of this research show thata law that will be implemented, must be considered not only textually but also contextually. A hadith sometimes applies permanently and continuously, and can change dynamically. The law depends on a certain 'illat, if the 'illat is lost, then the law will also disappear, and vice versa. This study explains that understanding the social background and the place in which a hadith appears is important, because it can prevent the meaning of a hadith from being mixed up with personal prejudices or things that come out of the zahir meaning of a text.